Analisis Jumlah Pengangguran, Belanja Langsung, dan Pengeluaran Perkapita Terhadap Kemiskinan Di Provinsi Kalimantan Selatan - Hidayat, Taufik; Suherty, Lina (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
One social problem that is hard to deal with is poverty, basically the poor are weak in their ability to do business and have limited access to social, educational, health and economic activities. This study is to see the effect of the variables of Total Unemployment, Direct Expenditure, and Per Capita Expenditure on poverty in the province of South Kalimantan 2015-2019. Using secondary data (pooled data) panel data regression models or a combination of time series and cross section data with the Fixed Effect Model (FEM) approach from 2015-2019 processed with E-Views 10 software. The regression results show a simultaneous significant effect of the independent variables, namely Total Unemployment, Direct Expenditure, and Government Expenditure on Total Poverty in South Kalimantan Province. While partially the significant effect only occurs in the Per Capita Expenditure variable.